Modeling and Analysis of Photo-Voltaic Solar Panel under Constant Electric Load - Salilih, Elias M.; Birhane, Yilma T. (Journal of Renewable Energy, 2019)
This paper presents modelling electrical performance of a typical PV panel/module (which is Kyocera 200GT) for constant electric loads (which are 2Ω, 4Ω, 6Ω, and 8Ω) under weather condition of a tropical region. The specific case of the city Jigjiga (9.35°N,42.8°E), located in the Eastern region of Ethiopia is considered. Electrical characteristics of the PV module are determined on the basis of detailed numerical algorithm, which was designed based on tested numerical technique from reviewed articles. The overall evaluation of the hourly variation in the electrical performance of the PV module is done by means of graphical technique, which determines the operating point of the PV module on voltage vs. current plane for each load, and the performance of the PV panel is compared for each load. The 4Ω electric load resulted in highest daily energy output of the PV panel on a daily basis for 11 days of the month of January (out of 12 considered days), but in the last day it resulted in a poorer performance with respect to the other two electrical loads (i.e., 6Ω and 8Ω electric loads).